2018
DOI: 10.1200/po.17.00172
|View full text |Cite
|
Sign up to set email alerts
|

BRAF in Lung Cancers: Analysis of Patient Cases Reveals Recurrent BRAF Mutations, Fusions, Kinase Duplications, and Concurrent Alterations

Abstract: Purpose Dabrafenib and trametinib are approved for the management of advanced non–small-cell lung cancers (NSCLCs) that harbor BRAF V600E mutations. Small series and pan-cancer analyses have identified non-V600 alterations as therapeutic targets. We sought to examine a large genomic data set to comprehensively characterize non-V600 B RAF alterations in lung cancer. Patients and Methods A total of 23,396 patients with lung cancer provided data to assay with comprehensive genomic profiling. Data were reviewed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…We confirmed that TP53, EGFR, KRAS, and NF1 were among the most often comutated genes in BRAF-mutant and BRAF-focally amplified tumors, consistent with previous reports. 36 In addition, we found that KRAS mutations were enriched in cases having class 3 BRAF mutations, which is also consistent with previous reports, 13,37 and preclinical data highlighting that these kinase-impaired alterations require additional RAS activation (e.g., KRAS mutations) or receptor tyrosine kinase activation (e.g., EGFR mutations) to promote cell growth and survival. 19,20 We also found that there was a significant association between NF1 mutations and class 2 BRAF mutations compared with class 1 (p ¼ 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…We confirmed that TP53, EGFR, KRAS, and NF1 were among the most often comutated genes in BRAF-mutant and BRAF-focally amplified tumors, consistent with previous reports. 36 In addition, we found that KRAS mutations were enriched in cases having class 3 BRAF mutations, which is also consistent with previous reports, 13,37 and preclinical data highlighting that these kinase-impaired alterations require additional RAS activation (e.g., KRAS mutations) or receptor tyrosine kinase activation (e.g., EGFR mutations) to promote cell growth and survival. 19,20 We also found that there was a significant association between NF1 mutations and class 2 BRAF mutations compared with class 1 (p ¼ 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…[23][24][25] Of the nine unique partners identified among 10 cases with BRAF fusions in this report, aspartylglucosaminidase (AGA)-BRAF and Arf-GAP with GTPase, ANK repeat and PH domain-containing protein 3 (AGAP3)-BRAF fusions have been reported in NSCLC, whereas KIAA1549-BRAF was identified in other tumors. Among the recently reported 21 distinct BRAF partners in NSCLC 25 , SALL2-BRAF is a novel fusion not reported previously. SALL2 contains four separate zinc finger domains which can bind to DNA and function as a transcription repressor as well as interact with SV40 large T antigen.…”
Section: Discussionmentioning
confidence: 87%
“…FGFR fusions were identified in approximately 0.2% of NSCLC cases from a large series of 26,054 patients and included one patient that had clinical benefit to an investigational FGFR inhibitor [90]. Similarly, low frequencies have been identified for BRAF fusions (0.2-2.8%) [91,92], MET fusions (0.04%) [93], and EGFR fusions (0.08%) [94]. Owing to the rarity of these fusion drivers and the limited epidemiological and clinical characterization of these cohorts, our understanding of the incidence of BM and intracranial efficacy of targeted therapies is limited.…”
Section: Other Rare Fusions In Nsclcmentioning
confidence: 99%